BOOK REVIEW: Schaik, Carel van – Michel, Kai: „The Good Book of Human Nature: An Evolutionary Reading of the Bible”. Hachette Book Group; USA; 2016; 480 pages; ISBN: 0465074707 - Kristóf LEGÉNDY (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The book co-authored by primatologist Carel van Schaik and historian Kai Michel offers a truly interesting reading for theologists and scientists alike. They examine the Bible as a historical record of the cultural evolution of Homo sapiens. Their basic thesis is that the texts of the Bible came into being during the cultural evolution from a hunter-gatherer way of life to a settled agricultural lifestyle, even if they were not composed as a direct result of the revolution of farming (as the two events were thousands of years apart). The Bible was written by countless authors, but God was not one of them – claim the co-authors. In fact, the working approach and basic concept of their book views the spiritual reading of the Bible as merely a subsequent addition or extra layer, and thus it was primarily written for those open to a purely scientific exegesis of the texts of the Bible, those willing to forgo its moral-spiritual interpretation. There is no room for me to present every point made in the book step by step from Genesis up to the Gospels – partly because it is a work of nearly 500 pages –, therefore I will only give highlights of what the co-authors mean by an evolutionary reading of the Bible.